The representation of other by European women in Africa in XX and XXI centuries: about autobiographical novels of Karen Blixen, Claude Njiké-Bergeret, Stefanie Zweig, Stefanie Gercke, Corinne Hofmann and Francesca Marciano - (:unkn) unknown (My University, 2012)
As far as people deals with community, there are singular routes which change their situations. By so doing, desires of foreign countries, fascinations of others are reasons that moreover brought European women to sojourn in African countries during different periods. For instance, it is the case of Franco-cameroonian Claude-Njiké Bergeret, the "White queen" of Bangangte kingdom; it is the case of the Danish Karen Blixen, the "Ngong queen"; German women as Stefanie Zweig and Stefanie Gercke are not neglected. The first, because of political reasons found refugee in Kenya whereas the second, who didn't obey her parents, was sacked and sent to South-Africa. The woman of Switzerland Corinne Hofmann, after going bankrupt, felt in love with a massaï warrior and became his wife. It is finally the British-Italian Francesca Marciano, who, after losing unfortunately her father, decided to travel to Kenya for safaris, in order to forget such unhappy memories. In fact, those women wrote autobiographical novels as (Ma passion africaine, La Ferme africaine, Une enfance africaine, Mon retour d'Afrique, La Massaï blanche, L'Africaine) which relate their daily histories, tells about their life and experience in African spheres, despite the fact that these spaces are linguistically and culturally diverse. So, if these novels show proof of love and affection of Migrants for Africa and Africans, and at that time, their passion and sympathy for these people, its hide to much clichés, racial prejudgments on other, which are discovered through deeply imagology study.
Keywords: African Research